Habitat suitability model for the lesser spotted woodpecker (Dryobates minor) in Scania, Sweden - Rostedt,Elin (2025)
Across Europe, breeding bird species are decreasing in several types of habitats. Deciduous forest specialist birds are facing a loss of habitat due to the forest management that removes important key components in the forest, e.g. dead wood. Already in Sweden three woodpecker species that are deciduous forest specialist have decreased in population: one has become locally extinct (middle spotted woodpecker Leiopicus medius), and another have faced a major decrease in population (white-backed woodpecker Dendrocopos leucotos). The third woodpecker species, the lesser spotted woodpecker (Dryobates minor), is still a widespread species in Sweden, compared to the other two. However, it is decreasing, and to keep the population at a satisfying level and try to increase the number of pairs, conservation work needs to be applied. To know where the conservation efforts is needed the most, a habitat suitability model would be useful. This model should be able to detect areas where the habitat matches the demands from the lesser spotted woodpecker. In this project, a habitat suitability model has been made and developed, with a connecting fieldwork in study squares to test the model. In total, 40 squares have been surveyed, and 21 lesser spotted woodpecker territories were found. After developing the model and adding a forest classification, the model could accurately detect forest stands with high quality. However, further development and tests are needed before the model could be applied for forest management recommendations, but with this project a habitat suitability model for the lesser spotted woodpecker is well on its way.